Electrochemical Activation of Carbon-Coated SiO2 Anode Materials for High-Performance Li-Ion Batteries - Dong, Xue; Woo, Chaeheon; Oh, Seungbae; Kim, Yeongjin; Zhang, Xiaojie; Choi, Kyung Hwan; Kang, Jinsu; Bang, Hyeon Seok; Jeon, Jiho; Oh, Hyung Suk; Kim, Dongju; Yu, Hak Ki; et al. (ACS Applied Energy Materials, 2024)
A silicon-based anode is one of the most promising anode materials for high-current-density lithium-ion batteries (LIBs). However, the volume expansion of pure Si and the complex synthesis of SiOx make their practical application challenging. On the other hand, SiO2, as another alternative to Si-based anodes, has attractive properties such as high theoretical capacity, abundance of elements, cost-effectiveness, and high mechanical strength. Nevertheless, due to its intrinsic poor electrochemical activity for lithiation, it is challenging to apply it as an anode. Therefore, to apply SiO2 as an anode with attractive properties, the electrochemical activation of SiO2 should be addressed. In this work, a carbon coating of SiO2 using polydopamine (C@SiO2) and potentiostatic activation of C@SiO2 are proposed to enhance the electrochemical activity of the C@SiO2 anode. The C@SiO2 anode, which is activated into Li4SiO4 and Si phases through hours of potentiostatic procedures, exhibits an excellent reversible capacity of 735.43 mAh g-1 at the 100th cycle. Furthermore, the activated C@SiO2 anode exhibits excellent full cell performance, indicating its potential application in high-performance LIBs. These results demonstrate that the proposed activation method for C@SiO2 anode materials can be applied to the preparation of SiO2-based anodes with excellent electrochemical performance for high-performance LIBs.
Keywords: Anode material; Carbon coating; Coating of SiO2 using polydopamine composite; Electrochemical activation; Ion batteries; Polydopamine; Property; SiO 2; SiO2-based anode; C@SiO2 composites; carbon coating; electrochemical activation; Li-ion battery; SiO2-based anode